A layered high energy storage density and high energy storage efficiency ceramic medium and preparation method thereof
By adopting alternately stacked high-polarization strength and high-pressure-resistant strength dielectric layers in lead-free energy storage ceramic media, combined with casting and sintering processes, the energy storage density and energy storage of lead-free ceramic media are solved. The problem of difficulty in synergistically improving efficiency has achieved high energy storage density and high energy storage efficiency.
Patent Information
- Application Number
- CN202310670794.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-06-07
AI Technical Summary
The energy storage density and energy storage efficiency of existing lead-free energy storage ceramic media are difficult to be synergistically enhanced, and the sintering matching ability of layered heterocemics is poor, which limits the improvement of the overall performance of the material.
The microstructure and performance of ceramic media are optimized by using high polarization strength dielectric layers of different materials and layered layer with high pressure resistance and high energy storage efficiency dielectric layers.
It has achieved high energy storage density and high energy storage efficiency of lead-free ceramic media, and has excellent performance of two different materials. It overcomes the problem of difficult to improve energy storage density and energy storage efficiency in the existing technology, and improves sintering. Matchability.
Smart Images

Figure CN116874295B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage ceramic media, and in particular relates to a layered ceramic medium with high energy storage density and high energy storage efficiency and a preparation method thereof. Background Art
[0002] With the increasing demand for non-renewable energy such as coal and oil, there is an urgent need to develop clean renewable energy and efficient energy storage and conversion technologies. Batteries, electrochemical capacitors and dielectric capacitors are currently the main types of electrical energy storage devices. In comparison, dielectric capacitors have the characteristics of high power density, fast charging and discharging speed, safety and reliability, and play an important role in the pulse systems of laser weapons, electromagnetic launchers, hybrid electric vehicles and other equipment. According to the type and thickness of the dielectric material used in dielectric capacitors, they can be roughly divided into thin film dielectric capacitors, polymer-based thick film dielectric capacitors and bulk ceramic dielectric capacitors. Although polymers and thin film dielectrics can withstand higher electric field strengths due to their thin thickness, the thin thickness limits the improvement of the total energy density. Ceramic dielectrics are easy to prepare into multilayer ceramic capacitors, and the preparation technology is relatively mature, making energy storage ceramic capacitors receive widespread attention in recent years.
[0003] Generally speaking, the energy storage performance of ceramic dielectrics can be calculated from the measured hysteresis loop, and the area enclosed by the hysteresis loop is expressed as the energy loss density (W loss ), and the releasable energy storage density (W rec ) and energy storage efficiency (η) are calculated using the following formula:
[0004]
[0005] η=W rec / (W rec +W loss )×100% (2)
[0006] Where P max , P r , P and E represent the maximum polarization intensity, residual polarization intensity, polarization intensity and electric field intensity respectively. Based on the above formula, it can be seen that a large P max , small P r High compressive strength is the key to high energy storage performance. Among many ceramic systems, antiferroelectric materials show a large P due to their unique double hysteresis loop characteristics. max , which can be ignored rAs well as moderate compressive strength, it is easy to obtain higher energy storage performance. However, most high-performance antiferroelectric ceramics contain heavy metal Pb elements, which are not conducive to environmental protection and human health and safety. Up to now, lead-free ceramic dielectrics have great differences in energy storage performance compared with lead-based antiferroelectric ceramic materials due to the difficulty in simultaneously improving the maximum polarization intensity, residual polarization intensity and compressive strength. There is an urgent need to significantly improve the energy storage density and energy storage efficiency of lead-free ceramic dielectrics.
[0007] The currently reported preparation methods for lead-free energy storage ceramic media are mainly traditional granulation and unidirectional pressure molding processes. The ceramic materials prepared by this method are usually thicker (>500μm) and need to be polished to 100-200μm before electrical performance testing and energy storage performance calculation, which will inevitably increase the preparation cost and preparation cycle; and it is difficult to directly obtain high-quality thin-layer ceramic samples with a thickness of less than 100μm. Although the tape casting process is easy to prepare high-quality thin-layer ceramic media, the research on layered energy storage ceramics is extremely slow due to factors such as sintering matching, and it mainly focuses on the layered structure design of similar composition materials, resulting in the energy storage density and energy storage efficiency of lead-free energy storage ceramics. It is always difficult to significantly improve. Summary of the invention
[0008] In order to solve the above problems existing in the prior art, the present invention provides a layered high energy storage density and high energy storage efficiency ceramic medium and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0009] The first aspect of the present invention provides a layered high energy storage density and high energy storage efficiency ceramic medium, wherein the layered high energy storage density and high energy storage efficiency ceramic medium is a layered structure formed by alternating first and second dielectric layers, wherein the first dielectric layer is a high polarization strength dielectric layer, and the material of the high polarization strength dielectric layer includes (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25 TiO3, wherein x=0.30-0.40, y=0.05-0.15; the second dielectric layer is a dielectric layer with high compressive strength and high energy storage efficiency, and the materials of the dielectric layer with high compressive strength and high energy storage efficiency include (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, wherein z=0.25-0.35; the minimum thickness of the layered structure is 25μm.
[0010] The second aspect of the present invention provides a method for preparing a layered ceramic medium with high energy storage density and high energy storage efficiency, comprising the steps of:
[0011] Weigh corresponding oxides or carbonates according to the chemical formulas of the first material and the second material to obtain a first raw material and a second raw material, wherein the first material has a high polarization strength and the second material has a high compressive strength and a high energy storage efficiency;
[0012] The first raw material and the second raw material are respectively subjected to a first ball milling for 4-24 hours; and are dried at 80-100° C.;
[0013] The raw materials after the first ball milling and drying are calcined at 800-900°C for 2-4h to obtain the pre-synthesized phase composition;
[0014] The pre-synthesized phase components are respectively subjected to a second ball milling, and the ball milling time is 4-24 hours;
[0015] The raw materials after the second ball milling are dried at 80-100°C and sieved to obtain ceramic powder;
[0016] Firstly, the first organic solution is mixed for 4 to 6 hours, and then the second organic solution, the binder and the ceramic powder are added to the first organic solution and mixed again for 4 to 6 hours to obtain the first ceramic slurry and the second ceramic slurry for tape casting;
[0017] The first ceramic slurry and the second ceramic slurry are respectively prepared by tape casting process to obtain a high polarization strength film, a high compressive strength film and a high energy storage efficiency film; wherein the height of the scraper in the tape casting process is 80-200 μm;
[0018] The high polarization strength film and the high compressive strength and high energy storage efficiency film are cut, laminated, pressed and other processes to obtain ceramic green bodies with different layered structures;
[0019] The ceramic green body is subjected to a debinding treatment at 550-600° C. with a heat preservation time of 8-10 hours, and then the debinded ceramic green body is sintered under closed conditions to finally obtain the layered high energy storage density and high energy storage efficiency ceramic medium.
[0020] Preferably, the first raw material comprises (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25 TiO3, wherein x=0.30-0.40, y=0.05-0.15, and the second raw material includes (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, wherein z=0.25-0.35.
[0021] Preferably, the (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 corresponding oxides or carbonates include Bi2O3, Fe2O3, BaCO3, TiO2, ZnO and Ta2O5; the Bi 0.39 Na 0.36 Sr 0.25 The oxides or carbonates corresponding to TiO3 include Bi2O3, Na2CO3, SrCO3 and TiO2; the oxides or carbonates corresponding to the (1-z)SrTiO3-zBiFeO3 include SrCO3, TiO2, Bi2O3 and Fe2O3; the oxides or carbonates corresponding to the BaBi2Nb2O9 include BaCO3, Bi2O3 and Nb2O5.
[0022] Preferably, the first type of organic solution is a mixed solution of anhydrous ethanol, butanone and triolein, and the mass ratio of anhydrous ethanol, butanone and triolein is: 40-60:80-120:3-6.
[0023] Preferably, the amount of butanone added to the first organic solution is 80%-100% of the mass of the ceramic powder.
[0024] Preferably, the second type of organic solution is a mixed solution of dibutyl phthalate and polyethylene glycol, and the mass ratio of dibutyl phthalate to polyethylene glycol is 1:1.
[0025] Preferably, the added amount of dibutyl phthalate and polyethylene glycol in the second organic solution is 2%-5% of the mass of the ceramic powder.
[0026] Preferably, the amount of the binder added is 8%-15% of the mass of the ceramic powder.
[0027] Preferably, the first type of organic solution is mixed by ball milling, and the ball milling medium includes zirconium oxide balls, wherein the amount of zirconium oxide balls added is 1.5-2.5 times the mass of the ceramic powder.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The layered high energy storage density and high energy storage efficiency ceramic medium and its preparation method of the present invention are ceramic mediums formed by alternating high polarization strength dielectric layers, high compressive strength and high energy storage efficiency dielectric layers of different materials, which can combine the excellent performance of two different materials into one, not only improving the energy storage density of lead-free ceramics, but also promoting a significant improvement in energy storage efficiency, thereby obtaining excellent comprehensive performance. At the same time, the preparation method of the present invention can effectively improve the sintering matching problem of heterogeneous ceramics, and can overcome the problem that the energy storage density and energy storage efficiency of existing lead-free energy storage ceramic media are difficult to be synergistically enhanced, and obtain ceramic media with high energy storage density and high energy storage efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic structural diagram of a layered ceramic medium with high energy storage density and high energy storage efficiency provided by the present invention;
[0031] Figure 2 It is a schematic structural diagram of another layered ceramic medium with high energy storage density and high energy storage efficiency provided by the present invention;
[0032] Figure 3 It is a structural schematic diagram of another layered ceramic medium with high energy storage density and high energy storage efficiency provided by the present invention;
[0033] Figure 4 It is a schematic diagram of the structure of a layered ceramic medium with high energy storage density and high energy storage efficiency prepared in Example 1 of the present invention;
[0034] Figure 5 This is a graph showing the test results of the hysteresis loop of the layered high energy storage density and high energy storage efficiency ceramic medium prepared in Example 1 of the present invention;
[0035] Figure 6 Schematic diagram of the structure of a layered ceramic medium with high energy storage density and high energy storage efficiency prepared in Example 2 of the present invention;
[0036] Figure 7 This is a graph showing the hysteresis loop test results of the layered high energy storage density and high energy storage efficiency ceramic medium prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0038] At present, the methods to improve the energy storage performance of lead-free ceramic dielectrics mainly focus on element doping, grain size and domain structure regulation, and core-shell structure construction. Although in recent years, there has been increasing attention paid to the fact that layered structures can improve the energy storage performance of lead-free ceramic dielectrics, related research has been slow due to factors such as sintering matching, and the commonly used matrix materials of different dielectric layers are of the same composition. For example, Yuan et al. from Xi'an Jiaotong University used a chemical coating method to obtain BaTiO3@SiO2 powder with a core-shell structure, and then designed and prepared a layered ceramic material composed of BaTiO3 and BaTiO3@SiO2 dielectric layers, obtaining a 1.80 J / cm 3 The releasable energy density and energy storage efficiency of 71.5% were obtained. Li et al. from Huazhong University of Science and Technology used 0.65Bi with high polarization strength. 0.5 Na 0.5 TiO3-0.35SrTiO3 and 0.45Bi with high energy storage efficiency 0.5 Na 0.5 TiO3-0.55Sr 0.7 Bi 0.2 The layered structure of TiO3 dielectric material was designed, and the effect of the number of interfaces on the breakdown behavior and polarization characteristics of layered ceramics was studied. Finally, 4.48 J / cm 3 Although these studies have improved the energy storage density and efficiency of lead-free ceramic dielectrics to a certain extent, the base materials of the two layers of dielectric materials used are the same, and the excellent performance of ceramic dielectrics with different material compositions cannot be complemented. It is still difficult to significantly improve the energy storage density and efficiency at the same time.
[0039] Based on this, the present invention proposes a layered high energy storage density and high energy storage efficiency ceramic medium and a preparation method thereof, which can better overcome the shortcomings of existing lead-free energy storage ceramic media, such as the difficulty in synergistically enhancing the energy storage density and energy storage efficiency, and the poor sintering matching of layered heterogeneous ceramics, thereby improving the research and development efficiency of lead-free ceramic media with high energy storage characteristics.
[0040] The first aspect of the present invention discloses a layered high energy storage density and high energy storage efficiency ceramic medium, see Figure 1 , Figure 1 The present invention is a layered high energy storage density and high energy storage efficiency ceramic medium, which is a layered structure formed by alternately stacking a first dielectric layer 1 and a second dielectric layer 2. The first dielectric layer 1 is a high polarization strength dielectric layer, and the material of the high polarization strength dielectric layer includes (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25TiO3, wherein x=0.30-0.40, y=0.05-0.15; the second dielectric layer 2 is a dielectric layer with high compressive strength and high energy storage efficiency, and the materials of the dielectric layer with high compressive strength and high energy storage efficiency include (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, wherein z=0.25-0.35; the minimum thickness of the layered structure is 25μm.
[0041] That is, the layered high energy storage density and high energy storage efficiency ceramic medium of the present invention may have a layered structure that is a combination of any high polarization strength dielectric layer and any high compressive strength and high energy storage efficiency dielectric layer, such as (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and (1-z)SrTiO3-zBiFeO3, which can be Bi 0.39 Na 0.36 Sr 0.25 TiO3 and BaBi2Nb2O9, or (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and BaBi2Nb2O9, or Bi 0.39 Na 0.36 Sr 0.25 TiO3 and (1-z)SrTiO3-zBiFeO3. The minimum thickness of the layered structure can reach 25μm, and the maximum thickness is not limited. Different layer thicknesses can be selected according to actual use requirements.
[0042] In addition, it should be noted that the layered structure of the ceramic dielectric of the present invention is not limited to a single-layer stacked structure consisting of a first dielectric layer and a second dielectric layer, and can be any stacked combination of the first dielectric layer and the second dielectric layer, for example, it can be a layered structure consisting of two first dielectric layers and one second dielectric layer, it can be a layered structure consisting of one first dielectric layer and two second dielectric layers, it can also be a layered structure consisting of two first dielectric layers and three second dielectric layers, and so on. Figure 2 and Figure 3 As shown. You can choose different layouts according to actual usage requirements.
[0043] The layered high energy storage density and high energy storage efficiency ceramic medium of the present invention is formed by alternating high polarization strength dielectric layers, high compressive strength and high energy storage efficiency dielectric layers of different materials, and can combine the excellent performance of two different materials into one, not only improving the energy storage density of lead-free ceramics, but also promoting a significant improvement in energy storage efficiency, thereby obtaining excellent comprehensive performance. In addition, the thickness of the ceramic medium of the present invention can be as low as 25 μm, which is much lower than the thickness of traditional granulated and pressed ceramic media, and can be directly tested for electrical properties and calculated for energy storage performance without polishing, saving preparation costs and preparation cycles.
[0044] The second aspect of the present invention provides a method for preparing a layered ceramic medium with high energy storage density and high energy storage efficiency, comprising the following steps:
[0045] S1. According to the chemical formulas of the first material and the second material, the corresponding oxides or carbonates are weighed respectively to obtain the first raw material and the second raw material, wherein the first material has high polarization strength, and the second material has high compressive strength and high energy storage efficiency.
[0046] The first material in this step includes (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25 TiO3, where x=0.30-0.40, y=0.05-0.15, the second material includes (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, where z=0.25-0.35.
[0047] According to the chemical formula of the first material and the second material, the corresponding oxides or carbonates are weighed respectively, that is, the first material is (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3, then weigh Bi2O3, Fe2O3, BaCO3, TiO2, ZnO and Ta2O5 accordingly; the first material is Bi 0.39 Na 0.36 Sr 0.25 If TiO3 is selected, Bi2O3, Na2CO3, SrCO3 and TiO2 are weighed accordingly; if the second material is (1-z)SrTiO3-zBiFeO3, SrCO3, TiO2, Bi2O3 and Fe2O3 are weighed accordingly; if BaBi2Nb2O9 is selected as the second material, BaCO3, Bi2O3 and Nb2O5 are weighed accordingly.
[0048] It should be noted that the oxides or carbonates corresponding to the first material and the second material are preferably of analytical grade.
[0049] S2. The first raw material and the second raw material are respectively subjected to a first ball milling for 4-24 hours; and are dried at 80-100°C.
[0050] The first raw material and the second raw material are respectively subjected to the first ball milling, so that the substances in the first raw material are uniformly mixed, and the substances in the second raw material are uniformly mixed. The ball milling media used in the first ball milling are zirconium oxide balls and anhydrous ethanol.
[0051] S3. The raw materials after the first ball milling and drying are calcined at 800-900° C. for 2-4 hours to obtain the pre-synthesized phase composition.
[0052] Specifically, the calcination in this step can be carried out in a crucible made of alumina, zirconia or the like.
[0053] S4. The pre-synthesized phase components are respectively subjected to a second ball milling, and the ball milling time is 4-24h.
[0054] The purpose of the second ball milling is to make the pre-synthesized raw material powder particles as fine as possible, so as to facilitate the subsequent acquisition of high-quality tape-casting slurry and ceramic membrane.
[0055] At the same time, as a preferred solution, during the second ball milling, 0.1-0.2wt% MnO2 or 0.1-0.2wt% MnCO3 or 0.1-0.2wt% Mn3O4 can be added according to the mass ratio of the raw material powder, the purpose is to prevent the iron from changing its valence at high temperature and changing its performance, and to adjust the sintering temperature so that the sintering temperatures of the two materials are close and the sintering matching is improved. The added MnO2 or MnCO3 or Mn3O4 preferably has a purity of ≥99%.
[0056] S5. Dry the raw materials after the second ball milling at 80-100° C. and sieve to obtain ceramic powder.
[0057] Specifically, the sieving in this step can be performed through a 120-mesh sieve.
[0058] S6. First, mix the first type of organic solution for 4 to 6 hours, then add the second type of organic solution, a binder and ceramic powder to the first type of organic solution and mix again for 4 to 6 hours to obtain a first ceramic slurry and a second ceramic slurry for tape casting.
[0059] The first type of organic solution is a mixed solution of anhydrous ethanol, butanone and triolein, and the mass ratio of anhydrous ethanol, butanone and triolein is 40-60:80-120:3-6. Within this ratio range, the "skinning" phenomenon of the slurry surface caused by the drying speed of the cast film can be effectively reduced, and the agglomeration of powder particles can be suppressed, thereby improving the dispersion and uniformity of the slurry.
[0060] The second type of organic solution is a mixed solution of dibutyl phthalate and polyethylene glycol, and the mass ratio of dibutyl phthalate to polyethylene glycol is 1: 1. Within this ratio range, the obtained cast film has excellent flexibility, processability and plasticity.
[0061] The binder used in this step is preferably polyvinyl butyral.
[0062] In addition, in order to achieve a better dissolution effect and further improve the film-forming quality, in this step, the amount of butanone added to the first organic solution is 80%-100% of the mass of the ceramic powder, the amount of dibutyl phthalate and polyethylene glycol added to the second organic solution is 2%-5% of the mass of the ceramic powder, and the amount of the binder added is 8%-15% of the mass of the ceramic powder.
[0063] It should be noted that the first type of organic solution mixing can be carried out by ball milling and magnetic stirring process, preferably by ball milling process, the ball milling medium includes zirconia balls, wherein the amount of zirconia balls added is 1.5-2.5 times the mass of the ceramic powder.
[0064] The casting slurry obtained in this step according to the above ratios has very good fluidity, and a high-quality thin-layer casting film can be obtained without the need for a vacuum degassing (removing bubbles from the slurry) process.
[0065] S7. Prepare the first ceramic slurry and the second ceramic slurry through tape casting process to obtain a high polarization strength film, a high compressive strength film and a high energy storage efficiency film respectively; wherein the height of the scraper in the tape casting process is 80-200 μm.
[0066] The prepared high polarization strength membrane, high compressive strength and high energy storage efficiency membrane are placed in a clean and dry environment at room temperature to allow the volatile organic matter to fully volatilize.
[0067] S8. The high polarization strength membrane, high compressive strength membrane and high energy storage efficiency membrane are cut, laminated, pressed and other processes to obtain ceramic green bodies with different layered structures.
[0068] The pressing process in this step is preferably:
[0069] At 30-60°C, the pressures of 50MPa, 100MPa, 150MPa, 200MPa and 250MPa are applied in sequence, and the holding time at each pressure is 8-10 minutes. This pressing method can eliminate the pores between the membranes as much as possible and improve the quality of the membranes.
[0070] S9. Debinding the ceramic green body at 550-600°C with a heat preservation time of 8-10 hours, and then sintering the debinded ceramic green body under closed conditions to finally obtain a layered ceramic medium with high energy storage density and high energy storage efficiency.
[0071] In order to further improve the quality of the ceramic medium, the sintering process in this step is preferably:
[0072] The temperature was raised from room temperature to 1060-1200°C at a heating rate of 3-5°C / min, then lowered to 960-1080°C at a cooling rate of 15-20°C / min and kept at this temperature for 2-4h, and then naturally cooled to room temperature in the furnace.
[0073] The layered high energy storage density and high energy storage efficiency ceramic medium and the preparation method thereof of the present invention are specifically described below in conjunction with specific embodiments.
[0074] Embodiment 1
[0075] The layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment, the material of the high polarization strength dielectric layer is 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta 2 / 3 )O3; the material of the dielectric layer with high compressive strength and high energy storage efficiency is BaBi2Nb2O9. The cross-sectional diagram of the layered ceramic dielectric is shown in Figure 1 shown.
[0076] The preparation method of the layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment comprises the following steps:
[0077] (1) Bi2O3, Fe2O3, BaCO3, TiO2, ZnO, Nb2O5 and Ta2O5 with a purity greater than 98% are selected as raw materials for layered high energy storage density and high energy storage efficiency ceramic media, and the raw materials are prepared according to the chemical formula 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta 2 / 3 )O3 and BaBi2Nb2O9 weigh 80 grams of the corresponding raw materials respectively;
[0078] (2) The weighed raw materials are mixed uniformly by ball milling (first ball milling), and dried at 80° C. to obtain initial raw material powder, wherein the ball milling media used are zirconium oxide balls and anhydrous ethanol, the amounts of zirconium oxide balls and anhydrous ethanol added are 150 g and 100 ml, respectively, and the ball milling time is 4 h;
[0079] (3) The raw material powder was placed in a zirconia crucible and calcined for 2 h to obtain a pre-synthesized phase composition, wherein 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta 2 / 3 )O3 and BaBi2Nb2O9 were calcined at 800℃, and the heating rate was 5℃ / min;
[0080] (4) Weigh 50 g of the calcined raw material and add 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta 2 / 3 )O3, adding 0.2wt% MnO2 (purity ≥ 99%), and placing it in a ball mill for a second ball milling to make the pre-synthesized raw material powder particles as fine as possible, so as to facilitate the later acquisition of high-quality tape-casting slurry and ceramic film, wherein the ball milling media used are zirconium oxide balls and anhydrous ethanol, the addition amounts of zirconium oxide balls and anhydrous ethanol are 100 g and 60 ml respectively, and the ball milling time is 24 h;
[0081] (5) The raw material after the second ball milling was dried at 80°C and passed through a 120-mesh sieve to obtain 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta 2 / 3 )O3 and BaBi2Nb2O9 ceramic powders;
[0082] (6) 40 g of zirconium oxide balls, 9 g of anhydrous ethanol, 20 g of butanone, and 0.8 g of triolein were weighed and placed in a 150 ml ball mill at 300 rpm for 4 h. Then, 0.7 g of dibutyl phthalate, 0.7 g of polyethylene glycol, 1.8 g of polyvinyl butyral, and 20 g of 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2Ta 2 / 3 )O3 or 20 g of BaBi2Nb2O9 ceramic powder, and again ball milled at a speed of 300 rpm for 4 h to obtain a ceramic slurry for tape casting;
[0083] (7) The ceramic slurry obtained above was used for tape casting to prepare 0.60BiFeO3-0.34BaTiO3-0.06Ba(Zn 1 / 2 Ta2 / 3 )O3 ceramic membrane and BaBi2Nb2O9 ceramic membrane with high compressive strength and high energy storage efficiency were placed in a clean and dry environment at room temperature for 2 days, wherein the height of the scraper during the tape casting process was 80 μm;
[0084] (8) The ceramic membrane obtained above is subjected to cutting, lamination, pressing and other processes to obtain ceramic green bodies with different layered structures, wherein the pressing process is carried out at 40° C. using pressures of 50 MPa, 100 MPa, 150 MPa, 200 MPa, and 250 MPa in sequence, and the holding time at each pressure is 8 minutes. The lamination process is as follows: Figure 4 As shown;
[0085] (9) The obtained ceramic body is subjected to a binder removal treatment at 550°C with a holding time of 10 hours, and then the debinding ceramic body is sintered under closed conditions to obtain a layered lead-free ceramic sample with high energy storage density and high energy storage efficiency. The sintering process is to increase the temperature from room temperature to 1060°C at a heating rate of 5°C / min, and then decrease the temperature to 960°C at a cooling rate of 15°C / min and hold the temperature for 2 hours, and then naturally cool to room temperature in the furnace to obtain the layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment.
[0086] The hysteresis loops of the layered high energy storage density and high energy storage efficiency ceramic medium prepared in this embodiment under different electric field strengths were tested using a ferroelectric analyzer. Figure 5 The effective energy storage density of the layered ceramic of this embodiment calculated based on formulas (1) and (2) at an electric field strength of 230 kV / cm is 0.6 J / cm 3 , the energy storage efficiency is 86%.
[0087] Embodiment 2
[0088] The layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment, the material of the high polarization strength dielectric layer is Bi 0.39 Na 0.36 Sr 0.25 TiO3; the material of the high compressive strength and high energy storage efficiency dielectric layer is 0.65SrTiO3-0.35BiFeO3.
[0089] The preparation method of the layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment comprises the following steps:
[0090] (1) Bi2O3, Fe2O3, SrCO3, Na2CO3 and TiO2 with a purity greater than 98% are selected as raw materials for the layered high energy storage density and high energy storage efficiency ceramic medium of this embodiment, and are respectively prepared according to the chemical formula Bi 0.39 Na 0.36 Sr0.25 TiO3 and 0.65SrTiO3-0.35BiFeO3 weigh a total of 80 grams of the above corresponding raw materials;
[0091] (2) The weighed raw materials are mixed uniformly by ball milling (first ball milling), and dried at 100° C. to obtain initial raw material powder, wherein the ball milling media used are zirconium oxide balls and anhydrous ethanol, the amounts of zirconium oxide balls and anhydrous ethanol added are 150 g and 100 ml, respectively, and the ball milling time is 24 h;
[0092] (3) The raw material powder is placed in an alumina crucible and calcined for 4 hours to obtain a pre-synthesized phase composition, wherein Bi 0.39 Na 0.36 Sr 0.25 The calcination temperatures of TiO3 and 0.65SrTiO3-0.35BiFeO3 were 850℃ and 900℃, respectively, and the heating rate was 3℃ / min;
[0093] (4) Weigh 50 g of the calcined raw material, add 0.1 wt% MnCO3 (purity ≥ 99%) to 0.65SrTiO3-0.35BiFeO3, and place it in a ball mill for a second ball milling to make the pre-synthesized raw material powder particles as fine as possible to facilitate the subsequent acquisition of high-quality tape-casting slurry and ceramic film. The ball milling media used are zirconium oxide balls and anhydrous ethanol. The added amounts of zirconium oxide balls and anhydrous ethanol are 100 g and 60 ml, respectively, and the ball milling time is 24 h;
[0094] (5) The raw material after the second ball milling was dried at 100°C and passed through a 120-mesh sieve to obtain Bi 0.39 Na 0.36 Sr 0.25 TiO3 and 0.65SrTiO3-0.35BiFeO3 ceramic powders;
[0095] (6) 40 g of zirconium oxide balls, 9 g of anhydrous ethanol, 20 g of butanone, and 0.8 g of triolein were weighed and placed in a 150 ml ball mill at 500 rpm for 6 h. Then, 0.8 g of dibutyl phthalate, 0.8 g of polyethylene glycol, 1.8 g of polyvinyl butyral, and 20 g of Bi were weighed and added. 0.39 Na 0.36 Sr 0.25 TiO3 or 20 g of 0.65SrTiO3-0.35BiFeO3 ceramic powder was ball-milled again at a speed of 500 rpm for 6 h to obtain a ceramic slurry for tape casting;
[0096] (7) The ceramic slurry obtained above was used for tape casting to prepare Bi with high polarization strength.039 Na 036 Sr 025 The TiO3 ceramic film and the 0.65SrTiO3-0.35BiFeO3 ceramic film with high compressive strength and high energy storage efficiency were placed in a clean and dry environment for 2 days at room temperature. The higher the scraper height, the thicker the ceramic film obtained by tape casting. In order to obtain thinner ceramic films and ceramic media while ensuring uniformity, the height of the scraper during the tape casting process of this embodiment is 120μm, and the thickness of the ceramic film after drying is about 10μm;
[0097] (8) The ceramic membrane obtained above is cut, laminated, pressed, etc. Figure 6 The layered ceramic green body shown in the figure, wherein the pressing process is to pressurize at 45°C with pressures of 50MPa, 100MPa, 150MPa, 200MPa, and 250MPa in sequence, and the holding time at each pressure is 10 minutes;
[0098] (9) The obtained ceramic body is subjected to a debinding treatment at 600°C with a holding time of 8 h. The debinding ceramic body is then sintered in a closed condition by buried firing to obtain a layered lead-free ceramic sample with high energy storage density and high energy storage efficiency. The sintering process is to increase the temperature from room temperature to 1220°C at a heating rate of 3°C / min, then decrease the temperature to 1080°C at a cooling rate of 20°C / min and hold the temperature for 3 h, and then naturally cool to room temperature in the furnace.
[0099] Since the ceramic film obtained by tape casting in this embodiment is relatively thin, the total thickness of the layered ceramic medium prepared by lamination and sintering is only 25 μm, and it can be plated with electrodes for electrical performance testing without thinning. The hysteresis loop of the prepared layered ceramic is tested using a ferroelectric analyzer. Figure 7 The effective energy storage density of the layered ceramic of this embodiment calculated based on formulas (1) and (2) at an electric field strength of 710 kV / cm is 9.05 J / cm 3 , the corresponding energy storage efficiency can reach more than 95%, while achieving higher energy storage density and energy storage efficiency.
[0100] The layered high energy storage density and high energy storage efficiency ceramic medium and the preparation method thereof of the present invention are ceramic mediums formed by alternating high polarization strength dielectric layers, high compressive strength and high energy storage efficiency dielectric layers, which can combine the excellent performance of two different materials into one, not only improving the energy storage density of lead-free ceramics, but also promoting a significant improvement in energy storage efficiency, thereby obtaining excellent comprehensive performance. At the same time, the preparation method of the present invention can effectively improve the sintering matching problem of layered heterogeneous ceramics, and can overcome the problem that the energy storage density and energy storage efficiency of existing lead-free energy storage ceramic media are difficult to be synergistically enhanced, thereby obtaining a ceramic medium with high energy storage density and high energy storage efficiency.
[0101] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A layered high energy storage density and high energy storage efficiency ceramic medium, characterized in that: The layered high energy storage density and high energy storage efficiency ceramic medium is a layered structure formed by alternately stacking a first dielectric layer and a second dielectric layer, wherein the first dielectric layer is a high polarization strength dielectric layer, and the material of the high polarization strength dielectric layer includes (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25 TiO3, wherein x=0.30-0.40, y=0.05-0.15; the second dielectric layer is a dielectric layer with high compressive strength and high energy storage efficiency, and the materials of the dielectric layer with high compressive strength and high energy storage efficiency include (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, wherein z=0.25-0.35; the minimum thickness of the layered structure is 25μm.
2. A method for preparing a layered ceramic medium with high energy storage density and high energy storage efficiency, characterized in that: Includes steps: According to the chemical formula of the first material and the second material, the corresponding oxides or carbonates are weighed respectively to obtain the first raw material and the second raw material, wherein the first material has high polarization strength, and the second material has high compressive strength and high energy storage efficiency; the first raw material includes (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 and Bi 0.39 Na 0.36 Sr 0.25 TiO3, wherein x=0.30-0.40, y=0.05-0.15, the second raw material comprises (1-z)SrTiO3-zBiFeO3 and BaBi2Nb2O9, wherein z=0.25-0.35; The first raw material and the second raw material are respectively subjected to a first ball milling for 4-24 hours; and are dried at 80-100° C.; The raw materials after the first ball milling and drying are calcined at 800-900°C for 2-4h to obtain the pre-synthesized phase composition; The pre-synthesized phase components are respectively subjected to a second ball milling, and the ball milling time is 4-24 hours; The raw materials after the second ball milling are dried at 80-100°C and sieved to obtain ceramic powder; First, the first organic solution is mixed for 4-6 hours, and then the second organic solution, the binder and the ceramic powder are added to the first organic solution and mixed again for 4-6 hours to obtain the first ceramic slurry and the second ceramic slurry for tape casting; The first ceramic slurry and the second ceramic slurry are respectively prepared by tape casting process to obtain a high polarization strength film, a high compressive strength film and a high energy storage efficiency film; wherein the height of the scraper in the tape casting process is 80-200 μm; The high polarization strength film and the high compressive strength and high energy storage efficiency film are cut, laminated and pressed to obtain ceramic green bodies with different layered structures; The ceramic green body is subjected to a debinding treatment at 550-600° C. with a heat preservation time of 8-10 hours, and then the debinded ceramic green body is sintered under closed conditions to finally obtain the layered high energy storage density and high energy storage efficiency ceramic medium.
3. The preparation method according to claim 2, characterized in that: The (1-xy)BiFeO3-xBaTiO3-yBa(Zn 1 / 2 Ta 2 / 3 )O3 corresponding oxides or carbonates include Bi2O3, Fe2O3, BaCO3, TiO2, ZnO and Ta2O5; the Bi 0.39 Na 0.36 Sr 0.25 The oxides or carbonates corresponding to TiO3 include Bi2O3, Na2CO3, SrCO3 and TiO2; the oxides or carbonates corresponding to the (1-z)SrTiO3-zBiFeO3 include SrCO3, TiO2, Bi2O3 and Fe2O3; the oxides or carbonates corresponding to the BaBi2Nb2O9 include BaCO3, Bi2O3 and Nb2O5.
4. The preparation method according to claim 2, characterized in that: The first type of organic solution is a mixed solution of anhydrous ethanol, butanone and triolein, and the mass ratio of anhydrous ethanol, butanone and triolein is: 40-60:80-120:3-6.
5. The preparation method according to claim 4, characterized in that: The amount of butanone added to the first type of organic solution is 80%-100% of the mass of the ceramic powder.
6. The preparation method according to claim 2, characterized in that: The second type of organic solution is a mixed solution of dibutyl phthalate and polyethylene glycol, and the mass ratio of dibutyl phthalate to polyethylene glycol is 1:
1.
7. The preparation method according to claim 6, characterized in that: The added amounts of dibutyl phthalate and polyethylene glycol in the second organic solution are both 2%-5% of the mass of the ceramic powder.
8. The preparation method according to claim 2, characterized in that: The added amount of the binder is 8%-15% of the mass of the ceramic powder.
9. The preparation method according to claim 2, characterized in that: The first type of organic solution is mixed by ball milling process, and the ball milling medium includes zirconium oxide balls, wherein the amount of zirconium oxide balls added is 1.5-2.5 times the mass of the ceramic powder.
Citation Information
Patent Citations
KR20230099465A